Institutional Habitus Around the Evaluation. (Des)Encounter Between Measurement and Understanding - Sánchez-Sánchez, Gerardo Ignacio; Jara-Amigo, Ximena Elizabeth (Revista Electrónica Educare, 2022)
Objective. The goal is to understand the habitus that school organizations develop around educational evaluation. The work was done with special education, preschool, primary, and secondary teachers. The teachers’ own theoretical and practical perceptions and conceptions of the various areas of their pedagogical work are defined by the institution where they work and its influences. Method. The research was developed with qualitative methodology parameters of transeccional type with a level of exploratory-descriptive depth. Through an intensive approach, the semi-structured interview was applied to 40 teachers in postgraduate programs, seeking the meaning of the teaching staff’s experiences. The information was processed through narrative analysis. Discussion. The results show the presence of a paradoxical habitus around evaluation, which configures it as a culture of measurement, quantification, and control, subtracting opportunities to transform it into a space of debate, reflection, and collaboration. Conclusions. It is concluded that the evaluation developed in the organizational contexts of the school is debated between the (dis)agreement of its social functions and its pedagogical functions. The projection of results shows that the evaluation constitutes, in teachers’ initial and continuous training processes, one of the weaknesses of the educational practice. In the field of intentions, the urgent need to turn it into a process that enables pedagogical function is outlined, integrating the teaching, learning, and evaluation units.